Competence, Accountability on Audit Quality: Auditor Ethics as Moderating Variable - Nurlinda Nurlinda; Nurwanah Nurwanah (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study examines and determines the effect of competence and accountability on audit quality with auditor ethics as a moderating variable. This research is quantitative research with a descriptive approach and statistical analysis. The population in this study were all auditors at KAP in Makassar City, amounting to 38 people. The sampling technique used was the census sampling technique. Data sources are primary data collected by distributing questionnaires to all respondents. The statistical method used to test the hypothesis is to use multiple correlations with the help of SmartPLS software; after all the data in this study is collected, then data analysis is carried out consisting of descriptive statistical analysis, measurement model tests, or outer models consisting of (convergent validity), discriminant validity, composite reliability) and structural model tests or inner models were evaluated using R-square for the dependent construct and direct and indirect hypothesis testing. The results showed that competence and accountability had a positive and significant effect on audit quality, auditor ethics were able to moderate competence on audit quality, and auditor ethics were able to moderate accountability on audit quality.